Experimental Evaluation of Automatic Tuning of PID Controllers for an Electro-Mechanical System. Issue 1 (July 2017) - Wang, Liuping; Freeman, Chris; Rogers, Eric
Abstract: Integrating processes are widely encountered in electro-mechanical systems and other areas. Automatic tuning of PID controllers for this type of system requires special consideration since the underlying system is unstable. Using relay feedback control in a closed-loop setting, an auto-tuner is designed to systematically find the controller parameters using a frequency sampling filter model. The performance of this auto-tuner is evaluated on an electro-mechanical experimental test facility that can be configured to operate in either as a single-input, single-output or multiple-input, multiple-output system. The experimental results demonstrate that when the interaction the between control loops is weak, the auto-tuner produces closed-loop performance that matches the specification, but this performance gradually decays as the level of interaction increases. The experimental results can also serve as experimental benchmarks to compare competing designs.